Indirect Controls and Performance of Public Universities in Nigeria - Nurudeen, Abdulfatai Olanrewaju (Journal of Technology Management and Business, 2024)
Emerging efficiency issues, unsatisfactory performance, inappropriate procedures or evaluations and lack of transparency from the public organizations necessitates the implementation of series of techniques used by the management to align the goals of employee with that of organization to avoid waste, fraud and mismanagement. Despite this, effort on administration and management of Nigerian universities is close to failure. In lieu of this, the study appraised the personnel control and cultural control’s effect on the performance of the public universities. Using PLS-SEM to analysed the data obtained with questionnaire from 12 selected universities in the South-western Nigeria, findings revealed that personnel control is positively and significantly related to the performance of public universities; likewise the cultural control has positive and significant effect on the performance of the public universities in South-western Nigeria. Study concludes that efficient personnel control and effective cultural control procedure are capable of transforming the performance of the public universities. The study recommends that recruitment process and other personnel control techniques should be objective and not on political favours. Also, the universities management should intensify the efforts on instituting the vision and mission of the universities into the code of conducts in the institution.